DESIGNING DESKTOP-BASED LEARNING MEDIA USING EDUCATIONAL GAME APPLICATIONS IN INTRODUCTORY ACCOUNTING COURSES - Firda Rahmawati; Kartika Dewi Sri Susilowati; Nurafni Eltivia (Yayasan Education and Social Center, 2022)
This study aims to determine the effect of desktop game application design on the subject of Introduction to Accounting 2 with the topic of inventory at the Department of Accounting, State Polytechnic of Malang. In this study, the technique used is Research and Development and Model Analysis, Design, Development, Implementation, Evaluation (ADDIE) but is only limited to the Analysis, Design, and Development (ADD) stage. The main software used in making this educational game is the python framework, namely Pygame and the Pycharm application as a Python development. The survey was conducted at one of the universities in Malang, namely the Malang State Polytechnic which is located at Jalan Soekarno Hatta No. 9, Jatimulyo Malang City